Short-Run Elasticity of Substitution - Error Correction Model - Martin Lukáèik; Karol Szomolányi; Adriana Lukáèiková (Institute of Economic Research (IER), 2017)
Research background: The value of the elasticity of the substitution has been a subject of the research around the world in last decades. It affects the qualitative and quantitative answers to a host of economic questions. Purpose of the article: We suggest the co-integration estimation form to estimate short-run elasticity of substitution. Using U.S. NIPA aggregate time series we estimate aggregate short-run elasticity of substitution. In comparison with estimations in economic literature, we confirm theoretical assumptions described in the research background. Methodology/methods: Different econometric estimation forms are used to estimate elasticity of the substitution coefficient. One possibility is a constant elasticity of substitution production function linearization. Others come from the first-order conditions of a representative firm expressing factor demand functions. Error correction models are natural and elegant way to estimate the forms with non-stationary data. However, the use of error correction models in the factor demand econometric forms is useless for estimating a long-run elasticity of substitution coefficient. The co-integration relationship is given by the theoretical assumption of the labour share constancy in the long-run or by other underlying processes. Though, we can use this co-integration relationship to correct error term in the short-run estimation form. To estimate the short-run elasticity of substitution, we use Stock and Watson's estimation form. Stability, stationarity and serial correlation of residuals are tested by the relevant econometric tests. Findings: The value of aggregate short-run elasticity of substitution is closed to one. In comparison with other relevant theoretical and empirical papers, our results incline to the Cobb-Douglas aggregate production function in U.S. economy.
Keywords: C13; E23; E24; 330; short-run and long-run elasticity of substitution; aggregate and sectoral estimations; vector error correction model; labour demand of the profit maximizing firm